Study on the methane adsorption characteristics of coal with heterogeneous potential wells. (4th March 2020) - Zhou, Dong; Feng, Zengchao; Zhao, Yangsheng
Due to the various components and the complex inner structures, the coal has the heterogeneous adsorption potential wells. The methane adsorption laws of the coal with heterogeneous potential wells are theoretically analysed and experimentally studied. It is concluded that the coverage of the potential wells with different depth obeys the law of the logistic (S) curve with the parameters of the adsorption pressure and the temperature. During the methane adsorption in coal, the Langmuir parameter a of coal has a fluctuate growth with the adsorption pressure increase, which is indicated that the number of the potential wells in coal with different depth tends to increase with the depth decrease. The Langmuir parameter b shows decrease trend with the adsorption pressure increase as the methane molecules in coal tend to be adsorbed in the deep potential wells. The heterogeneous potential wells method (HPWM) for the methane isothermal adsorption amount calculation is put up. From the experiment, the high positive errors are shown in low adsorption pressures based on the Langmuir's equation while the high negative errors are shown in high adsorption pressures. The methane adsorption amount calculation based on the HPWM is much accurate than that based on the Langmuir equation. [Received: December 9, 2017; Accepted: April 19, 2018]